Analisis Pendapatan Dan Biaya Relevan Pada Peralihan Bisnis Offline To Online : Studi Kasus Pada Toko Elektronik Cahaya Bersinar - Mansyur, Maulana; Sharon Purba , Nico; Suria Manda , Gusganda; Yoga Pardistya, Irvan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The development of technology and the use of the internet is increasingly rapid, making many businesses make the transition from conventional sales to online businesses. This study aims to determine the increase in business profits by switching from offline to online with the analysis of revenue and relevant costs. Based on the results of the study, it is shown that switching from offline to online business profits can increase business based on revenue analysis and relevant costs for tactical decision making. The contribution of this research is that it can show that one of the techniques in increasing profits is to utilize technology and networks in doing business. In addition, this research can provide consideration of financial analysis techniques before making tactical decisions on business techniques